Reducing the Diagnostic Heterogeneity of Schizoaffective Disorder - Seldin, Katherine; Armstrong, Kristan; Schiff, Max L.; Heckers, Stephan (Frontiers in Psychiatry, 2017)
Objective: Clinical outcome studies of schizoaffective disorder patients have yielded conflicting results. One reason is the heterogeneity of samples drawn from the schizoaffective disorder population. Here we studied schizoaffective disorder patients who showed marked functional impairment and continuous signs of illness for at least 6 months (i.e., DSM criteria B and C for schizophrenia). Methods: We assessed 176 chronic psychosis patients with a structured interview (SCID-IV-TR) and the Diagnostic Interview for Genetic Studies (DIGS) schizoaffective disorder module. We diagnosed 114 patients with schizophrenia and 62 with schizoaffective disorder. The two groups were similar with regard to age, gender, and race. We tested for group differences in antecedent risk factors, clinical features, and functional outcome. Results: The schizoaffective disorder group differed from the schizophrenia group on two measures only: they showed higher rates of suicidality (more suicide attempts, p < 0.01; more hospitalizations to prevent suicide, p < 0.01) and higher anxiety disorder comorbidity (p < 0.01). Conclusions: When schizoaffective disorder patients meet DSM criteria B and C for schizophrenia, they resemble schizophrenia patients on several measures used to assess validity. The increased rate of anxiety disorder and suicidality warrants clinical attention. Our data suggest that a more explicit definition of schizoaffective disorder reduces heterogeneity and may increase validity.